Answer:
Step-by-step explanation:
The method applied in this scenario is called simple random sampling. A sample of 100 customers is chosen from a larger population of customers and each customer has the same chance of being selected for the survey at any given time. Also, the chance of selecting 100 customers from each store is the same during the sampling process. The order of sampling at each store does not follow a certain order, thus, It is different from systematic random sampling.
Answer:
30
Step-by-step explanation:
Probabilities are used to determine the chances of events
The value of the probability P(x < 24) is 0.7895
<h3>How to calculate the probability
P(x < 24)?</h3>
This is calculated as:
![P(x < 24) = \frac{n(x < 24)}{Total}](https://tex.z-dn.net/?f=P%28x%20%3C%2024%29%20%3D%20%5Cfrac%7Bn%28x%20%3C%2024%29%7D%7BTotal%7D)
So, we have:
![P(x < 24) = \frac{22 + 3 + 5}{22 + 3 + 5 + 4 + 4}](https://tex.z-dn.net/?f=P%28x%20%3C%2024%29%20%3D%20%5Cfrac%7B22%20%2B%203%20%2B%205%7D%7B22%20%2B%203%20%2B%205%20%2B%204%20%2B%204%7D)
Evaluate the sums
![P(x < 24) = \frac{30}{38}](https://tex.z-dn.net/?f=P%28x%20%3C%2024%29%20%3D%20%5Cfrac%7B30%7D%7B38%7D)
Evaluate the quotient
![P(x < 24) = 0.7895](https://tex.z-dn.net/?f=P%28x%20%3C%2024%29%20%3D%200.7895)
Hence, the value of the probability P(x < 24) is 0.7895
Read more about probabilities at:
brainly.com/question/9385303
Answer:
Step-by-step explanation:
The sum of two matrices is the sum of corresponding terms.
![\left[\begin{array}{ccc}3&1&0\\-1&2&4\\9&7&-2\end{array}\right] +\left[\begin{array}{ccc}5&2&4\\1&12&3\\11&3&-2\end{array}\right] =\left[\begin{array}{ccc}8&3&4\\0&14&7\\20&10&-4\end{array}\right]](https://tex.z-dn.net/?f=%5Cleft%5B%5Cbegin%7Barray%7D%7Bccc%7D3%261%260%5C%5C-1%262%264%5C%5C9%267%26-2%5Cend%7Barray%7D%5Cright%5D%20%2B%5Cleft%5B%5Cbegin%7Barray%7D%7Bccc%7D5%262%264%5C%5C1%2612%263%5C%5C11%263%26-2%5Cend%7Barray%7D%5Cright%5D%20%3D%5Cleft%5B%5Cbegin%7Barray%7D%7Bccc%7D8%263%264%5C%5C0%2614%267%5C%5C20%2610%26-4%5Cend%7Barray%7D%5Cright%5D)
Answer:
![(f\circ g)(x)= x + 4](https://tex.z-dn.net/?f=%28f%5Ccirc%20g%29%28x%29%3D%20x%20%2B%204)
Step-by-step explanation:
<u>Composite Function</u>
Given f(x) and g(x) as real functions, the composite function
is defined as:
![(f\circ g)(x)=f(g(x))](https://tex.z-dn.net/?f=%28f%5Ccirc%20g%29%28x%29%3Df%28g%28x%29%29)
It can be found by substituting g into f.
We are given the functions:
f(x) = -x + 3
g(x) = -x -1
Find
![(f\circ g)(x)=f(g(x))= - (-x -1) + 3](https://tex.z-dn.net/?f=%28f%5Ccirc%20g%29%28x%29%3Df%28g%28x%29%29%3D%20-%20%28-x%20-1%29%20%2B%203)
Removing parentheses:
![(f\circ g)(x)= x + 1 + 3](https://tex.z-dn.net/?f=%28f%5Ccirc%20g%29%28x%29%3D%20x%20%2B%201%20%2B%203)
Simplifying:
![\mathbf{(f\circ g)(x)= x + 4}](https://tex.z-dn.net/?f=%5Cmathbf%7B%28f%5Ccirc%20g%29%28x%29%3D%20x%20%2B%204%7D)